P3.44 Just google it! the impact of media coverage of an outbreak of high-level azithromycin resistant gonorrhoea on attendances, testing and diagnoses at local sexual health clinics. (8th July 2017) - Smolarchuk, C; Furegato, M; Mohammed, H; Town, K; Fifer, H; Wilson, J; Nardone, A; Hughes, G
Abstract : Introduction: An outbreak of high-level azithromycin resistant gonorrhoea, dubbed 'super gonorrhoea' in the mainstream media, emerged in Leeds, England in 2015 and has since spread to other parts of the country. We aimed to determine if media coverage affected online searches nationally and attendances, and gonorrhoea testing and diagnoses locally at sexual health clinics (SHCs). Methods: Google Trends was used to determine Relative Search Interest (RSI) for 'gonorrh*' and 'super gonorrh*' in England from 2015–2016. Using data from England's national STI surveillance system (GUMCADv2), an interrupted time series analysis was performed to compare the sex-stratified, weekly rates of attendances, and gonorrhoea testing and diagnoses at 6 SHCs in Leeds and in other affected areas. The analysis compared rates of events 6 weeks before and after initial media coverage of the outbreak in September 2015. Results: The RSI peaked during initial media coverage in September 2015 (100) with smaller peaks in December 2015 (47), April 2016 (72), and September 2016 (33), coinciding with subsequent coverage. The number of SHC attendances by women in Leeds rose after initial media coverage (p<0.01) by 36% (from 320 to 435/week), but there was only a 4% increase in attendances (from 326 to 340/week) by men (p=0.70). There was no change in rates of gonorrhoea tests or diagnoses in women (p=0.87 and 0.23) or men (p=0.51 and p=1.00). There were no significant increases in event rates in other areas with a high RSI including Birmingham, Manchester, London, Liverpool and Sheffield. Conclusion: Media coverage of the outbreak was associated temporally with increased online searches for gonorrhoea nationally, and female attendances at SHCs in Leeds only. This demonstrates opportunities for health promotion for the prevention and control of outbreaks and raises the question of how best to target such messaging to those populations and groups most likely to benefit from attending and being tested in SHCs.